The Role of the Setono Chicken Satay Industry in Improving Community Welfare from an Islamic Economic Perspective - Ahmaru, Moh Batu; Masykuroh, Ely (JURNAL MANAJEMEN MOTIVASI, 2025)
This study explores the role of the Setono Chicken Satay culinary industry in enhancing community welfare from an Islamic economic perspective. Using a qualitative approach and inductive analysis, the research finds that economic activities in this culinary village improve household income, housing conditions, and access to education. Social solidarity and the integration of Islamic values foster spiritual well-being and community stability. The industry serves as a model of sustainable development, balancing material, educational, health, and spiritual needs, thus exemplifying a harmonious and productive society